Dicamba: Dynamics in Straw (Maize) and Weed Control Effectiveness - Mundt, Tamara Thais [UNESP]; Gimenes Cotrick Gomes, Giovanna Larissa; Picoli Junior, Gilmar José; Lopez Ovejero, Ramiro Fernando; Domingues Velini, Edivaldo [UNESP]; Carbonari, Caio Antonio [UNESP] (MDPI, 2024)
Dicamba is a post-herbicide, showing some activity in soil, and its dynamics can be influenced by several factors, including the presence of straw. Brazil has more than 50% of its production area in a no-till system; thus, a good amount of the herbicide is intercepted by the straw. This study aimed to evaluate dicamba dynamics in straw and weed control efficacy when sprayed as a PRE herbicide. For this, five different studies were conducted: we utilized different straw amounts (1) and different drought periods (2) for straw sprayed with dicamba and dicamba + glyphosate to evaluate its release from straw, different straw amounts (3), different drought periods (4), and wet and dry straw (5) to evaluate pre-emergence weed control (Bidens pilosa and Ipomoea grandifolia) and dicamba availability in medium-texture soil. Around 80% of dicamba was released from the straw after 100 mm of rainfall. One day after dicamba application, 65–70% of dicamba was released from the straw with 20 mm of rainfall, while for 7 and 14 DAA, 60% was released. Dicamba was efficient in controlling the pre-emergence of both species studied, and the amount of straw did not interfere in weed control; however, dicamba was less available in the soil after rainfall when sprayed in the straw than when sprayed directly in the soil. Up to 80% of dicamba can be released from the straw after 100 mm of rainfall and weed control was efficient for the species studied; however, the carryover effect in sensitive crops might become an issue.
Keywords: Bidens pilosa; chemical control; environmental behavior; Ipomoea grandifolia; LCMSMS; no-till system; synthetic auxin herbicides